Biodegradation of a magnesium alloy implant in the intercondylar femoral notch showed an appropriate response to the synovial membrane in a rabbit model in vivo. (August 2014) - Ezechieli, Marco; Diekmann, Julia; Weizbauer, Andreas; Becher, Christoph; Willbold, Elmar; Helmecke, Patrick; Lucas, Arne; Schavan, Robert; Windhagen, Henning
Degradable magnesium alloys are promising biomaterials for orthopedic applications. The aim of this study was to evaluate the potential effects on both the synovial membrane (synovialis) and the synovial fluid (synovia) of the degradation products of a MgYREZr-pin implanted in the intercondylar femoral notch in a rabbit model. Thirty-six animals were randomized into two groups (MgYREZr or Ti6Al4V alloy) of 18 animals each. Each group was then divided into three subgroups with implantation periods of 1, 4, and 12 weeks, with six animals in each subgroup. The initial inflammatory reaction caused by the surgical trauma declined after 12 weeks of implantation, and elucidated a progressive recovery of the synovial membrane. Compared with control Ti6Al4V pins, there were no significant differences between the groups. However, after 12 weeks, recovery of the synovial membrane was more advanced in the titanium group, in which 92% showed no signs of synovitis, than in the magnesium group. A cytotoxicity test with L929 cells and human osteoblasts (HOB) was also conducted, according to EN ISO 10993-5/12, and no toxic leachable products were observed after 24 h of incubation. In conclusion, the MgYREZr alloy seems to be a suitable material for intra-articular degradable implants.